TVET Skills Gap Analysis in Electrical and Electronic Industry: Perspectives from Academicians and Industry Players - Rodzalan, Shazaitul Azreen; Mohd Noor, Noor Nazihah; Abdullah, Nor Hazana; Mohamed Saat, Maisarah (Journal of Technical Education and Training, 2022)
Skills mismatch or skill gap is a long-standing issue whereby the levels and types of the existing skills do not meet the needs of the job market. With no exception, this issue also become one of the challenges that facing by Technical and Vocational Education and Training (TVET). If this issue prolongs, it will lead to graduate unemployment, specifically in TVET. Therefore, this study aims to identify the occupational skills (including both soft and hard skills) that are perceived as important by those in public Higher Education Institutions (HEI) and the electrical and electronic (E&E) industry which represent the manufacturing industry. A total of 58 academicians from public HEI and 55 industry players from the E&E industry in Malaysia were chosen purposively. These academicians and industry players were selected as they are having experience in occupational skill and training in their respective institutions and industries. Questionnaires were distributed online to these targeted respondents. The results revealed that there are skills gaps in terms of both soft and hard skills, which all skills are skills related to the career in E&E industry. The outcomes of this study should enable the Ministry of Higher Education, mainly in TVET to devise strategies to improve graduate employability. They might also serve as additional evidence for the occurrence of skills mismatch.